Effect of Eu-implantation and annealing on the GaN quantum dots excitonic recombination - Peres, Marco (2013)
Undoped self-assembled GaN quantum dots (QD) stacked in superlattices (SL) with AlN spacer layers were submitted to thermal annealing treatments. Changes in the balance between the quantum confinement, strain state of the stacked heterostructures and quantum confined Stark effect lead to the observation of GaN QD excitonic recombination above and below the bulk GaN bandgap. In Eu-implanted SL structures, the GaN QD recombination was found to be dependent on the implantation fluence. For samples implanted with high fluence, a broad emission band at 2.7 eV was tentatively assigned to the emission of large blurred GaN QD present in the damage region of the implanted SL. This emission band is absent in the SL structures implanted with lower fluence and hence lower defect level. In both cases, high energy emission bands at approx. 3.9 eV suggest the presence of smaller dots for which the photoluminescence intensity was seen to be constant with increasing temperatures. Despite the fact that different deexcitation processes occur in undoped and Eu-implanted SL structures, the excitation population mechanisms were seen to be sample-independent. Two main absorption bands with maxima at approx. 4.1 and 4.7 to 4.9 eV are responsible for the population of the optically active centres in the SL samples.